Ceci n’est pas... L’immagine tradita - Di Vita, Vincenza (Mimesis Journal, 2016)
Cinzia Muscolino is an actress, an artist, set designer and costume designer. Arte facta is one of her creation in which the character of Helena Shida Smiecic, has a new identity with the appearance of Antonin Artaud. Using anagrams generated by the securities commissions from his artistic work, she creates true interactive performance, she raises questions to the viewer, acting on the imagination and common sense. The artistic research of Cinzia Muscolino is prompted by a true civic engagement. Vincenza Di Vita, identified the reasons of art in Muscolino, through illustrative images and an interview.